2021
DOI: 10.1021/acsapm.1c00616
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Engineering and Additive Manufacturing of Poly(styrene-b-isobutylene-b-styrene)

Abstract: Although polyisobutylene (PIB)-based thermoplastic elastomers (TPEs) possess a combination of unique properties (i.e., low permeability, high environmental and chemical stability, and excellent biocompatibility), they have not been explored for 3D printing. Poly­(styrene-b-isobutylene-b-styrene) (SIBS) is one of the most important PIB-based TPEs used in biomedical applications. Herein, we report, for the first time, the development of an efficient and low-cost 3D printing strategy of SIBS by fine-tuning its mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Filaments of SIBS/PPO blends with 1.75 mm diameter were prepared for FFF 3D printing. As we found earlier, [ 23 ] SIBS is unsuitable for FFF 3D printing due to its softness (43.7 shore A), which leads to filament buckling and extrusion failure. SIBS/PPO blends with 30–50 wt% PPO show substantially enhanced 3D printability (Table 1).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Filaments of SIBS/PPO blends with 1.75 mm diameter were prepared for FFF 3D printing. As we found earlier, [ 23 ] SIBS is unsuitable for FFF 3D printing due to its softness (43.7 shore A), which leads to filament buckling and extrusion failure. SIBS/PPO blends with 30–50 wt% PPO show substantially enhanced 3D printability (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…This comparative study shows that PPO has very high compatibility with SIBS, and that the addition of PPO has a similar effect on the supramolecular structure of SIBS as the addition of PS homopolymer. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A glass temperature well below room temperature is desirable for improving the mechanical properties of the matrix (faster return, less drift, in particular) but possibly worsens the Young moduli mismatch with a fiber of high modulus. In addition, the analysis of triaxiality in dog-bone-shaped specimens may be of interest in experiments involving samples with internal structuration, as, for example, 3D-printed objects described by Shen et al These authors showed that the printing angle, that is, the angle between the traveling direction of the nozzle and the long axis of the dog-bone, strongly affects the mechanical properties, especially the modulus. Triaxiality effects in the dog-bone-shaped samples could, in addition, affect the in-layer and interlayer failure modes.…”
Section: Resultsmentioning
confidence: 99%